Modifiable Factors Explain Socioeconomic Inequalities in Children's Dental Caries. (October 2019) - Peres, M.A.; Ju, X.; Mittinty, M.; Spencer, A.J.; Do, L.G.
The aim of this article was to quantify socioeconomic inequalities in dental caries experience among Australian children and to identify factors that explain area-level socioeconomic inequalities in children's dental caries. We used data from the National Child Oral Health Survey conducted in Australia between 2012 and 2014 ( n = 24, 664). Absolute and relative indices of socioeconomic inequalities in the dental caries experience in primary and permanent dentition (decayed, missing, and filled surfaces [dmfs] and DMFS, respectively) were estimated. In the first stage, we conducted multilevel negative binomial regressions to test the association between area-level Index of Relative Socioeconomic Advantage and Disadvantage (IRSAD) and dental caries experience (dmfs for 5- to 8-y-olds and DMFS for 9- to 14-y-olds) after adjustment for water fluoridation status, sociodemographics, oral health behaviors, pattern of dental visits, and sugar consumption. In the second stage, we performed Blinder-Oaxaca and Neumark decomposition analyses to identify factors that explain most of the area-level socioeconomic inequalities in dental caries. Children had a mean dmfs of 3.14 and a mean DMFS of 0.98 surfaces. Children living in the most disadvantaged and intermediately disadvantaged areas had 1.96 (95% confidence interval, 1.69–2.27) and 1.45 (1.26–1.68) times higher mean dmfs and 1.53 (1.36–1.72) and 1.43 (1.27–1.60) times higher mean DMFS than those living in the most advantaged areas, respectively. Water fluoridation status (33.6%), sugar consumption (22.1%), parental educational level (14.2%), and dental visit patterns (12.7%) were the main factors explaining area-level socioeconomic inequalities in dental caries in permanent dentition. Among all the factors considered, the factors that contributed most in explaining inequalities in primary dental caries were dental visits (30.3%), sugar consumption (20.7%), household income (20.0%), and water fluoridation status (15.9%). The inverse area-level socioeconomic inequality in dental caries was mainly explained by modifiable risk factors, such as lack of fluoridated water, high sugar consumption, and an unfavorable pattern of dental visits.